PERBANDINGAN RISIKO INKONTINENSIA URIN TIPE STRESS ANTARA PERSALINAN NORMAL DAN SECTIO CAESAREA DI POPULASI WANITA INDONESIA: SYSTEMATIC REVIEW DAN META-ANALISIS - Suryoadji, Kemal Akbar; As’syifa, Salsa Billa; Surya Putra, Abdul Hafiidh; Kusuma, Fitriyadi (Universitas Islam Indonesia, 2024)
ABSTRACTIntroduction: Stress urinary incontinence (SUI) is a common consequence of childbirthand pelvic floor dysfunction. The risk of SUI differs between vaginal delivery and cesareansection, but this comparison in the Indonesian female population remains unclear.Methods: This study is a systematic review and meta-analysis comparing the risk of SUIbetween vaginal delivery and cesarean section among Indonesian women using reviewmanager 5.4. application. Literature searches were conducted in PubMed, Scopus, andCochrane databases using relevant keywords.Results: Analysis of two studies involving 438 women revealed a lower risk of SUI in thecesarean section group (16 out of 233 women) compared to vaginal delivery (38 out of 205women). The combined risk ratio was 0.41 (95% CI: 0.22–0.75), indicating that cesareansection significantly reduces the risk of SUI compared to vaginal delivery.Conclusion: Cesarean section is associated with a lower risk of SUI compared to vaginaldelivery in the Indonesian female population. These findings may assist clinicians andpatients in making informed decisions about childbirth methods.